A new dynamic distribution model for Antarctic krill reveals interactions with their environment, predators, and the commercial fishery in the south Scotia Sea region - Freer, Jennifer J.; Warwick-Evans, Victoria; Skaret, Georg; Krafft, Bjørn A.; Fielding, Sophie; Trathan, Philip N. (Limnology and Oceanography, 2025)
The management strategy for the Antarctic krill (Euphausia superba) fishery is being revised. A key aim is to spatially and temporally allocate catches in a manner that minimizes impacts to both the krill stock and dependent predators. This process requires spatial information on the distribution and abundance of krill, yet gaps exist for an important fishing area surrounding the South Orkney Islands in the south Scotia Sea. To fill this need, we create a dynamic distribution model for krill in this region. We used data from a spatially and temporally consistent acoustic survey (2011-2020) and year-specific environmental covariates within a two-part hurdle model. The model successfully captured observed spatial and temporal patterns in krill density. The covariates found to be most important included distance from shelf break, distance from summer sea ice extent, and salinity. The northern and eastern shelf edges of the South Orkney Islands were areas of consistently high krill density and displayed strong spatial overlap between intense fishing activity and foraging chinstrap penguins. High mean krill density was also linked to oceanographic features located within the Weddell Sea. Our data suggest that years in which these features were closer to the South Orkney shelf were also years of positive Southern Annular Mode and higher observed krill densities. Our findings highlight existing fishery?predator?prey overlap in the region and support the hypothesis that Weddell Sea oceanography may play a role in transporting krill into this region. These results will feed into the next phase of krill fisheries management assessment.
Keywords: Scotiahavet; Sør-Orknøyene; Sørishavet; Weddellhavet; ekkolodd; fiskerier; krill; oseanografi; plankton

Assessing trawls size selectivity in Antarctic krill: The role of sex and maturity stages - Krag, Ludvig Ahm; Brčić, Jure; Herrmann, Bent; Nalon, Marco; Krafft, Bjørn Arne (Regional Studies in Marine Science, 2025)
Understanding the connection between maturity stages and morphology in relation to size selectivity in trawls is essential for assessing the impact of various fishing gear on the population structures of harvested species, their fishing mortality rates, and the efficiency of the gear used. The Antarctic krill (Euphausia superba) fishery is the largest in the Southern Ocean by volume, and there is increasing interest in expanding the industry. The krill fishery employs different trawl designs and is not currently subject to technical regulations specifying the types of fishing gear and mesh sizes that can legally be used. There is a need to establish a robust model predicting size selectivity that includes the morphological variation in the population of krill. Male and female Antarctic krill are described with 12 maturity stages, from juveniles to sexually mature adults, each with distinct morphological features. The current study established a morphological description of each individual krill maturity stage to identify and parameterize what determines size selectivity using the FISHSELECT framework. This framework is used to predict size selectivity for each of the different stages in various mesh sizes and openings relevant to the krill fishery, in both actual and virtual populations. The results can be used to assess size selectivity for specific fishing gears and population structures, facilitating more accurate understanding and modeling of the fishery’s impact on the demographic composition of the krill stock.
Keywords: Sørishavet; fiskerier; fiskeriforvaltning; krill; marine økosystemer; plankton; populasjonsbiologi

Sex Differentiation and Long-Distance Gene Flow in the Elusive Antarctic Fish Aethotaxis mitopteryx - Schiavon, Luca; Desvignes, Thomas; Ronco, Fabrizia; Matschiner, Michael; Gastaldi, Martina; Koppetsch, Thore; Schrøder-Nielsen, Audun; Postlethwait, John H.; Prestanti, Alessia; Stranci, Federica; Ceballos, Santiago G.; Mark, Felix C.; et al. (Ecology and Evolution, 2025)
Understanding population connectivity in the marine realm is crucial for conserving biodiversity, managing fisheries, and predicting species responses to environmental change. This is particularly important in Antarctic waters, where unique evolutionary histories and extreme conditions shape marine biodiversity. The longfin icedevil Aethotaxis mitopteryx is an elusive notothenioid fish endemic to Antarctic waters. To explore population connectivity in A. mitopteryx, we used RAD-seq to investigate the genetic differentiation of two populations, one from the Eastern Weddell Sea and the other from the Eastern Antarctic Peninsula, two regions of ecological relevance greatly impacted by climate change. Despite spatial separation, analyses revealed no significant genetic differentiation between the two populations, suggesting extensive gene flow. A pronounced genetic distinction was, however, observed between males and females. This differentiation was largely localized to a specific chromosome, implying a genetic sex determination system with males being the heterogametic sex. These findings contribute novel insights into the genetic structure of A. mitopteryx populations and expand our understanding of genetic mechanisms in Antarctic fish. This study provides a foundation for further investigations into the evolutionary and ecological implications of sex chromosome differentiation in extreme environments.
Keywords: Sørishavet; Weddellhavet; biodiversitet; fiskerier; genetikk; klimaendringer; marin biologi; marin økologi

Sex Differentiation and Long-Distance Gene Flow in the Elusive Antarctic Fish Aethotaxis mitopteryx - Schiavon, Luca; Desvignes, Thomas; Ronco, Fabrizia; Matschiner, Michael; Gastaldi, Martina; Koppetsch, Thore; Schrøder-Nielsen, Audun; Postlethwait, John H.; Prestanti, Alessia; Stranci, Federica; Ceballos, Santiago G.; Mark, Felix C.; et al. (Ecology and Evolution, 2025)
Understanding population connectivity in the marine realm is crucial for conserving biodiversity, managing fisheries, and predicting species responses to environmental change. This is particularly important in Antarctic waters, where unique evolutionary histories and extreme conditions shape marine biodiversity. The longfin icedevil Aethotaxis mitopteryx is an elusive notothenioid fish endemic to Antarctic waters. To explore population connectivity in A. mitopteryx, we used RAD-seq to investigate the genetic differentiation of two populations, one from the Eastern Weddell Sea and the other from the Eastern Antarctic Peninsula, two regions of ecological relevance greatly impacted by climate change. Despite spatial separation, analyses revealed no significant genetic differentiation between the two populations, suggesting extensive gene flow. A pronounced genetic distinction was, however, observed between males and females. This differentiation was largely localized to a specific chromosome, implying a genetic sex determination system with males being the heterogametic sex. These findings contribute novel insights into the genetic structure of A. mitopteryx populations and expand our understanding of genetic mechanisms in Antarctic fish. This study provides a foundation for further investigations into the evolutionary and ecological implications of sex chromosome differentiation in extreme environments.
Keywords: Sørishavet; Weddellhavet; biodiversitet; fiskerier; genetikk; marin biologi; marin økologi

Automated krill body length estimation based on stereo camera images - Svantemann, Mette M; Krafft, Bjørn A; Thompson, Fletcher F; Zhang, Guosong; Krag, Ludvig A (ICES Journal of Marine Science, 2025)
The fishery for Antarctic krill (Euphausia superba) is the largest by tonnage in the Southern Ocean, and understanding its population dynamics is essential for the sustainable management of this fishery. The standard method for calculating Antarctic krill biomass relies on hydroacoustic survey data and incorporates krill body length data collected concurrently. Traditional scientific acoustic surveys involve manually measuring the body lengths of individual krill caught using fine- meshed nets or trawls along acoustic transects. This work is resource-demanding and could represent a source of human error. To address these challenges, we develop and test an alternative, more automated method for estimating krill body length data by employing an in-trawl stereo camera system. This system collects images that are automatically processed by a custom-trained machine learning model. The results from the machine learning model are then compared to manually measured krill subsampled from the total catch of the corresponding trawl hauls. We demonstrated the ability to extract body lengths from underwater images. However, our results highlighted uncertainties, which we propose addressing by incorporating more advanced camera technology and optimizing the observation section of the small-meshed two-layer krill trawl.
Keywords: Sørishavet; ekkolodd; fiskerier; fiskeriforvaltning; krill; marin biologi; plankton

Untangling the complexities of larval Antarctic krill overwintering success under climate change - Sylvester, Zephyr T; Veytia, Devi; Bahl, Alexis A; Bahlburg, Dominik; Benkort, Deborah; Bestley, Sophie; Cagdas, Bulut; Cleary, Alison C; Constable, Andrew; Corney, Stuart; Fach, Bettina A; Hellessey, Nicole; et al. (ICES Journal of Marine Science, 2025)
Antarctic krill (Euphausia superba) are integral to Southern Ocean pelagic ecosystems. Winters with extensive sea ice have been linked to high post-larval krill recruitment the following spring, suggesting that sea ice plays a critical role in larval overwinter survival. As the ocean warms and sea ice declines under climate change, understanding the mechanisms linking sea ice and krill recruitment is increasingly urgent. To address this, we developed a qualitative network model (QNM) that integrates evidence-based and hypothesized interactions to explore larval overwinter survival and growth under future climate scenarios in the southwest Atlantic sector. Our model highlights habitat-specific impacts, with substantial declines predicted for the North Antarctic Peninsula continental shelf due to reduced autumn primary productivity and warming. In contrast, survival may improve in open-ocean habitats under cooler scenarios that enhance sea-ice-associated processes, such as food availability and refuge. The inclusion of hypothesized mechanisms, such as sea-ice terraces providing refuge from predation, strengthened these conclusions and highlighted critical uncertainties, including the influence of glacial melt on food web dynamics. These findings demonstrate the value of QNMs in complementing quantitative approaches, offering a framework for identifying critical mechanisms, addressing knowledge gaps, and guiding future field and laboratory studies to improve predictions of krill responses to climate change.
Keywords: Sørishavet; fiskerier; klimaendringer; krill; oseanografi; plankton

Impact of krill (Euphausia superba) meal on growth performance of aquatic animals: A meta-analysis and prospective directions - Tran, Hung Quang; Nguyen, Tram Thi; Prokešová, Markéta Dvořáková; Øverland, Margareth; Gasco, Laura; Kumar, Vikas; Van Doan, Hien; Stejskal, Vlastimil (Animal Nutrition, 2025)
Antarctic krill meal (KM) (Euphausia superba) as a substitute for fishmeal in aquatic animal diets is gaining popularity worldwide. A quantitative approach investigating the efficacy of using this protein on the production performance of aquatic animals remains widely limited. Here, we employed a meta-analysis to quantify the overall effects (Hedges’g [g] value effect size) of KM on the specific growth rate (SGR), feed conversion ratio (FCR), protein efficiency ratio (PER), and survival rate (SR) of several aquaculture species. A total of 22 records published during 2006 to 2022 from different countries, targeting 14 aquatic species, were employed in the present study. Overall, KM has a high nutritional value relative to fishmeal, particularly from the high protein and amino acid composition. Dietary KM significantly increased the overall effect size of SGR (g = 1.92) (P = 0.001); the positive effect was illustrated in marine species (g = 1.32 to 9.10) (P < 0.05) and sturgeon (Acipenser gueldenstaedtii) (g = 6.59) (P < 0.001). The overall g value for FCR (−2.42) was significantly improved compared to the control group (P < 0.001). The inclusion of KM in aquatic animal diets did not affect g value of PER (1.52, 95% confidence interval: −1.04 to 4.07) and survival rate (0.08, 95% confidence interval: −0.63 to 0.79) (P = 0.252 and 0.208, respectively). The meta-regression models indicated that SGR of rainbow trout (Oncorhynchus mykiss) was significantly correlated with dietary KM by a positive linear model (P = 0.022). The cod and sturgeon (A. gueldenstaedtii) appeared to efficiently utilize krill-containing diets as illustrated by a negative linear model (P = 0.011 and P = 0.024, respectively) between dietary KM and FCR. Dietary KM positively correlated with PER for Atlantic cod (P = 0.021). Our meta-analysis highlighted the significant outcome of KM in diets for aquaculture species by reducing pressure on forage fish from marine resources and sparing edible foods. Specifically, including KM significantly reduced economic fish-in fish-out (eFIFO) in four taxa—the top forage fish consumers (P < 0.05): marine fish, salmon, shrimp, and trout. The meta-analysis revealed the decreased food-competition feedstuff in diets for important aquaculture species (P < 0.05) fed dietary KM. The outlook for efficient use of KM from marine resources in aquafeeds was elucidated in the present work.
Keywords: Sørishavet; akvakultur; fiskerier; krill; marin biologi; marin økologi; plankton

Field comparison of Antarctic krill (Euphausia superba) backscatter and aggregation types using NORTEK and SIMRAD echosounders - Annasawmy, Pavanee; Horne, John K.; Reiss, Christian S.; Cutter, George R.; Macaulay, Gavin J. (ICES Journal of Marine Science, 2024)
Temporal distributions of Antarctic krill (Euphausia superba) density and aggregation types were characterized and compared using Nortek Signature100 and SIMRAD Wideband Autonomous Transceiver (WBAT) upward-looking echosounders. Noise varied between the two echosounders. With the Signature100, it was necessary to correct data for background, transient, and impulse noises, while the WBAT data needed to be corrected for background noise only. For selected regions with no visible backscatter, the signal-to-noise ratio of Sv values (i.e. the ratio between the signal and the background noise level) did not vary between the two echosounders. Surface echo backscatter was similar during similar time periods. Descriptive metrics were used to quantify spatial and temporal krill vertical distributions: volume backscatter, mean depth, center of mass, inertia, equivalent area, aggregation index, and proportion occupied. Krill backscatter density differed between the two instruments but was detected at similar mean depths. Krill aggregations were identified at each mooring location and classified in three types based on morphological characteristics. Each type of aggregation shape differed at the two spatially separated moorings, while the acoustic density of each aggregation type was similar. The Signature100 detected a lower number of krill aggregations (n = 133) compared to the WBAT (n = 707). Although both instruments can be used for autonomous deployment and sampling of krill over extended periods, there is a strong caveat for the use of the Signature100 due to significant differences in noise characteristics and krill detection.
Keywords: Sørishavet; dataanalyse; ekkolodd; fiskerier; krill; marin biologi; plankton

KRILLSCAN: An automated open-source software for processing and analysis of echosounder data from the Antarctic krill fishery - Menze, Sebastian; Macaulay, Gavin J.; Zhang, Guosong; Lowther, Andrew D.; Krafft, Bjørn A. (Fisheries Management and Ecology, 2024)
Krillscan software was developed to automatically process echosounder data and achieve an accelerated and transparent analysis of backscatter data that allows calculation of target biomass. Herein, the fishery for Antarctic krill (Euphausia superba, Henceforth Krill) was used as a case study to develop the approach. Implementation of a sustainable management strategy for the krill fishery is complicated by a lack of regularly updated krill abundance data on spatiotemporal scales of the fishery. To increase krill biomass data availability, automatic echosounder data processing and swarm detection software was tested against traditional manual scrutinization with LSSS software and agreed with only minor offsets in estimated nautical area scattering coefficients. In addition to automatic processing and data transfer, Krillscan also has a graphical user interface to supervise automatic krill swarm detection. Echogram size can be compressed up to 100 times and raw data are processed faster than generated, thereby enabling near-real time analysis and data transfer. Compressed data can be transmitted online to allow fishing vessels to conduct surveys without having scientific personnel with special expertise on board.
Keywords: Sørishavet; dataanalyse; ekkolodd; fiskerier; krill; plankton

Regime Management at the Bottom of the Food Web - Gjelsvik Tiller, Rachel (The Journal of Environment & Development, 2010)
Fishing down the food chain is a controversial issue that demands further exploration. Redfeed is a marine species located on the second to last level on the food web. It is also one of the potential saviors of the aquaculture industry. The role of effective management of this species is of utmost importance to avoid the potential catastrophe associated with its overharvesting. Using a calculation of behavioral effectiveness, a blueprint redfeed regime is compared with the Convention for the Conservation of the Antarctic Marine Living Resources (CCAMLR), an ecosystem-based management regime with the now famous krill as its key species. Though the regimes are similar in nature, their geopolitical differences suggest that a future redfeed regime will be effective even though CCAMLR has not been. Ensuring that the redfeed is not merely incorporated into existing regimes, but is treated separately in an ecosystem-based regime, will alleviate the interplay this future redfeed regime otherwise would encounter.
Keywords: Antarktistraktaten; Sørishavet; fiskerier; internasjonal rett; krill; marin økologi; marine økosystemer; plankton; polarområdene

How fast do demersal longlines sink? - Robertson, Graham; Moe, Egil; Haugen, Roy; Wienecke, Barbara (Fisheries Research, 2003)
Longlines that sink fast reduce the time available to seabirds to attack baited hooks and are important in efforts to minimise seabird by-catch in longline fisheries. We measured sink rates in still seawater of longlines commonly used in the world’s demersal fisheries. Lines with integrated weight (lead cores) sank two to three times faster (45–52cm/s) than conventional (unweighted) lines. Conventional 9mm diameter lines made from polyester sank at 23cm/s compared to 18cm/s for 9mm Silver lines (blend of polyester, polyethylene and polypropylene). Samples of lines set by hand in still water sank significantly faster than longlines set from a fishing vessel, presumably because of the effect of the sea swell and upwellings from the propeller on the line set from the vessel.
Keywords: Sørishavet; fiskefartøy; fiskerier

Antarktisk krill : deteksjon - fangst - anvendelse; teknisk / økonomisk analyse - Fiskerstrand, Rolf (Universitetet i Trondheim Norges tekniske høgskole, Institutt for skipsprosjektering, 1979)
Keywords: Sørishavet; ekspedisjoner; fiskerier; krill; zooplankton; økonomi

Norsk fangst av antarktisk krill : teknisk/økonomisk analyse - Fiskerstrand, Rolf (Norges fiskerihøgskole, Universitetet i Trondheim, Norges tekniske høgskole, Institutt for marin prosjektering, 1979)
Keywords: Sørishavet; ekspedisjoner; fiskerier; historie; hvalfangst; krill; pelagisk; zooplankton; økonomi

Del IV: Hvalfangst - fangstnæring - Knudtzon, Hans Thomas (Norsk fiskeri- og fangsthåndbok : saltvannsfiskeriene : ferskvannsfiskeriene : ishavsfangsten : hvalfangsten, 1949)
Keywords: Sørishavet; fiskerier; historie; hvalfangere; hvalfangst; hvalfangstindustri; hvalfangstkvoter; hvalfangstregulering; hvalfangstselskaper; hvalindustri; internasjonal; næring; pelagisk; samarbeid; økonomi